2020
DOI: 10.1002/ana.25956
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Epilepsy in Infants with Tuberous Sclerosis Complex in the EPISTOP Trial

Abstract: Objective Epilepsy develops in 70 to 90% of children with tuberous sclerosis complex (TSC) and is often resistant to medication. Recently, the concept of preventive antiepileptic treatment to modify the natural history of epilepsy has been proposed. EPISTOP was a clinical trial designed to compare preventive versus conventional antiepileptic treatment in TSC infants. Methods In this multicenter study, 94 infants with TSC without seizure history were followed with monthl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
163
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 189 publications
(173 citation statements)
references
References 32 publications
3
163
0
7
Order By: Relevance
“…Looking forward, refinement of this predictive model with the inclusion of serial EEG data and EEG connectivity metrics will likely enhance its performance 60,61 . Additionally, preventative treatment of seizures with vigabatrin is currently being studied for TSC in Europe 62 and the United States (NCT02849457). Specific prediction of spasms based on our imaging methods may allow for improved risk stratification and limit exposure to vigabatrin for pre‐emptive treatment to those at higher risk.…”
Section: Discussionmentioning
confidence: 99%
“…Looking forward, refinement of this predictive model with the inclusion of serial EEG data and EEG connectivity metrics will likely enhance its performance 60,61 . Additionally, preventative treatment of seizures with vigabatrin is currently being studied for TSC in Europe 62 and the United States (NCT02849457). Specific prediction of spasms based on our imaging methods may allow for improved risk stratification and limit exposure to vigabatrin for pre‐emptive treatment to those at higher risk.…”
Section: Discussionmentioning
confidence: 99%
“…Our experience confirms the previously reported findings in children with TSC and supports the role of early seizure control-among other yet to be discovered factors-in preventing the development of ID, psychiatric comorbidities and drug resistance itself in the long term. 41 While analysing data about our adult population, we should consider that the outcome of these individuals in terms of seizure control and cognitive functioning surely reflects the therapeutic attitudes that were in use 20-40 years ago. Of note, Vigabatrin and mTOR inhibitors, which are now known to significantly improve the outcome of young patients with TSC, were not widely used at that time.…”
Section: Con Clus Ions/s Treng Ths and LI M Itati O N Smentioning
confidence: 99%
“…In the recent fenfluramine and CBD studies, caregivers and investigators reported greater improvements in global impression of change in the treatment groups than with placebo, 29,81 and in the fenfluramine study, those on higher dose fenfluramine had greater improvements in their quality of life inventory, executive function, and metacognitive index than those on placebo 82 . Preventative use of vigabatrin administered to 25 infants with TSC who had epileptifom activity on EEG, but no electrical or clinical seizures, was associated with reduced risk and severity of subsequent epilepsy, when compared to 29 TSC infants treated conventionally with vigabatrin for seizures 83 . Some ASMs for DEEs have been used for decades in some countries, such as STP in France and other parts of Europe, and CBD has recently been approved in the United States and Europe.…”
Section: New Medical Treatments In Deesmentioning
confidence: 84%
“…82 Preventative use of vigabatrin administered to 25 infants with TSC who had epileptifom activity on EEG, but no electrical or clinical seizures, was associated with reduced risk and severity of subsequent epilepsy, when compared to 29 TSC infants treated conventionally with vigabatrin for seizures. 83 Some ASMs for DEEs have been used for decades in some countries, such as STP in France and other parts of Europe, and CBD has recently been approved in the United States and Europe.…”
Section: Antiseizure Medicationsmentioning
confidence: 99%